A rare case of acute pancreatitis due to very severe hypertriglyceridemia treated with subcutaneous insulin and lipid lowering drugs - Bajaj, Tushar; Grandhe, Sundeep; Duong, Hanh; Ratnayake, Saman N. (AME Case Reports, 2019)
The diagnosis of acute pancreatitis in a patient requires the presence of two of the following three criteria: (I) acute onset of persistent, severe; (II) epigastric pain often radiating to the back, elevation in serum lipase or amylase to three times or greater than the upper limit of normal; (III) characteristic radiographic evidence hypertriglyceridemia is a potential cause of acute pancreatitis when levels are greater than 1,000 mg/dL. Very severe hypertriglyceridemia is classified as levels above 2,000 mg/dL. Management includes targeting pancreatitis with intravenous fluids, pain control, and nutritional support. While apheresis with therapeutic plasma exchange is a known option for severe hypertriglyceridemia, we present a rare case with management with intravenous fluids, subcutaneous insulin, statins, and fibrates in a patient with a triglyceride level of 12,234 mg/dL who presented with severe epigastric pain radiating to her back.